Analisis Penolakan Permohonan Isbat Nikah dan Akibat Hukumnya (Studi Kasus di Pengadilan Agama Kwandang) - Ainiyyah Lumula, Adelia Nurfatma; Rajak, Arafik; Moonti, Roy Marthen (Lembaga Pengembangan Kinerja Dosen, 2025)
The rejection of isbat nikah applications in religious court practice, particularly in the context of polygamy, is a complex issue with far-reaching implications for the legal status of marriage, the rights of wives and children, and legal certainty. This study aims to analyze the legal considerations of the panel of judges in rejecting the application for isbat nikah polygamy at the Kwandang Religious Court and to examine the legal consequences arising from the rejection. This research uses an empirical juridical method with a case approach, which is analyzed based on primary data in the form of court decisions and interviews with judges and related parties, and secondary data in the form of legal literature, legislation, and relevant legal journals. The results show that the rejection of polygamous marriage isbat nikah applications is generally caused by the non-fulfillment of substantive requirements as stipulated in Pasal 4 and 5 of Undang-Undang Nomor 1 Tahun 1974 concerning Marriage jo. Compilation of Islamic Law (KHI), such as the absence of permission from the first wife or the lack of proof of the reasons that allow polygamy. The legal consequences of this rejection include the formal non-recognition of the legal status of the second marriage, which has an impact on the non-fulfillment of the civil rights of the second wife and the children born, such as inheritance rights and citizenship status. This study recommends the need to strengthen legal education to the community as well as harmonization between state law and religious law to ensure the legal protection of women and children in the context of polygamy.